1983
DOI: 10.1037/0735-7044.97.5.697
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal motor cortex lesions in the rat: Absence of sparing of motor behaviors and impaired spatial learning concurrent with abnormal cerebral morphogenesis.

Abstract: Rats with removal of the motor cortex in adulthood were compared behaviorally and neuroanatomically with rats with similar removals at 4 days of age. The results suggest that neonatal ablation of the motor cortex of rats is more debilitating behaviorally than similar injury in adulthood and produces abnormal morphogenesis of the posterior neocortex. Neonatal lesions of the motor cortex produced more chronic abnormalities in movements of the distal effectors that accompany adult lesions (tongue, snout, and digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…The results of the present study are similar to those found after neonatal cortical stroke (Kolb and Holmes, 1983) and adds to current literature by describing the temporal and spatial progression of post-stroke cortical thinning in adult rat models. Additionally, by utilizing MRI, the present study is the first to confirm this morphological progression in vivo in an animal model and, to our knowledge, is the first to quantify the extent of residual tissue movement into the stroke infarct.…”
Section: Relevance To Present Literaturesupporting
confidence: 89%
See 3 more Smart Citations
“…The results of the present study are similar to those found after neonatal cortical stroke (Kolb and Holmes, 1983) and adds to current literature by describing the temporal and spatial progression of post-stroke cortical thinning in adult rat models. Additionally, by utilizing MRI, the present study is the first to confirm this morphological progression in vivo in an animal model and, to our knowledge, is the first to quantify the extent of residual tissue movement into the stroke infarct.…”
Section: Relevance To Present Literaturesupporting
confidence: 89%
“…First, it has been suggested that cortex can thin by moving into the infarct cavity. This would be especially notable in the pial strip model in which tissue can move into not only the infarct, but also into the cavity produced by the trephination itself (Adams et al, 1994;Kolb & Holmes, 1983;Navari et al, 1978;Whishaw, 2000;Xu et al, 2007). Second, all of the stroke models likely involve neuroinflammatory responses, secondary neurodegeneration, and apoptosis, which take place over time following the stroke (Chen et al, 2003;Bidmon et al, 1998;Pulsinelli, 1982;Witte et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kitten's brain matures faster, such that at 3 weeks of age it is comparable to that of a baby born at term. By comparison, nonhuman primates are born relatively more mature (Passing ham et aI., 1983) whereas the brain of the rat is considerably less mature at birth (Kolb and Holmes, 1983;Almli, 1984). (ii) The cat is an ad vanced mammal with a rich and extensively studied behavioral repertoire (see Olm stead, 1979, 1982) and thus allows for metabolic behavioral correlations.…”
mentioning
confidence: 99%